The effects of synaptic modulation on the vibrotactile responses of somatosensory cortical neurons studied by microinjection, microstimulation and a computational model - Vardar, Bige. (Thesis (Ph.D.)-Bogazici University. Institute of Biomedical Engineering, 2019., 2019)
In this thesis, we studied the eﬀects of synaptic modulation on the vibrotactile responses of somatosensory cortical neurons by three diﬀerent methods: microinjection, microstimulation and a computational model. First, we recorded single-unit spikes evoked by sinusoidal (duration: 500 ms; frequency: 5, 40, and 250 Hz; amplitude: 100 µm) stimulation of the glabrous skin. The changes in the responses were studied with microinjection of aCSF (sham), bicuculline, AMPA and NMDA near the isolated neurons in anesthetized rats. All drugs increased average ﬁring rates only during vibrotactile stimulation, and increased entrainment as measured by the vector strength of spike phases. The results suggest that three inhibitory factors shape the spike responses of the neurons. In a diﬀerent experiment, we electrically stimulated Basal forebrain (BF), the main source of cortical cholinergic inputs, of anesthetized rats while recording single-unit (n=87) spike activity in the SI cortex. The vibrotactile responses were measured with and without BF stimulation (0.5-ms bipolar pulses (50 µA) at 100 Hz for 0.5 s). BF activation had short-term and long-lasting signiﬁcant eﬀects on entrainment, but being eﬀective only at 5-Hz mechanical stimulation. BF activation did not cause signiﬁcant main eﬀects (regardless of cell type and layer) on the ﬁring rate measures. Long-lasting eﬀects of cholinergic activation on entrainment are dependent on cell type and layer, probably due to the projection pattern from BF. Lastly, a preliminary computational model was generated mimicking the vibrotactile responses observed in the ﬁrst experiment. By changing the model parameters, the effects of synaptic inputs can be simulated. Overall, this thesis may help to understand clinical conditions regarding excitation-inhibition balance and cholinergic modulation.|Keywords : Somatosensory, Attention, Cholinergic, GABAergic, Glutamatergic.
Keywords: Neural networks (Neurobiology); Somatosensory evoked potentials.; Attention.